Does off-farm labor relax farmers' credit constraints? Evidence from longitudinal data for Vietnam - Marco Stampini; Benjamin Davis (Institute for the Study of Labor (IZA), 2008)
We examine the relationship between participation in non-agricultural labor activities and farming production decisions, focusing on the use of inputs. In particular, we are interested in the hypothesis that income from non-agricultural labor relaxes credit constraints. Using longitudinal data for Vietnam from 1993-98, we find that households participating in non-agricultural labor activities, consistently with our hypothesis, spend significantly more on seeds, services, hired labor and livestock inputs.
urn:nbn:de:101:1-2008032059
Keywords: J43; 330; Rural labor markets; linkages; credit constraints; Vietnam; Landwirtschaftlicher Kleinbetrieb; Verschuldungsrestriktion; Nebenerwerbslandwirtschaft; Ländlicher Arbeitsmarkt; Vietnam